Interpersonal Communication of the Fatima Al-Fihri Qur'an House in Reducing Al-Qur'an Illiteracy in Berastagi, Karo District - Riris Silvia Tampubolon; Hasnun Jauhari Ritonga (Universitas Muhammadiyah Enrekang, 2023)
Interpersonal communication becomes a bridge to human social activity in living life and becomes an important study in the development of science. Knowledge and interpersonal communication are also needed in the development program of an agency or institution, organization and others such as education, social, religion and society. The problem of Al-Qur'an illiteracy is also influenced by Interpersonal communication. This study analyses how the Fatima Al-Fihri Qur'an House uses interpersonal communication to reduce Al-Qur'an literacy in Berastagi, Karo District. The method used in this research is a descriptive qualitative method by describing research findings in general descriptions in the form of words. Data collection techniques used in this study were observation, interviews and literature studies supported by theories relevant to research taken from literature reviews in the form of articles, books and data that support research. The results of the study describe that Rumah Qur'an Fatima Al-Fihri uses interpersonal communication with the theory put forward by R. Wayne Pace that interpersonal communication is carried out face to face and receives messages directly. This scientific study also contains social exchange theory in reducing Qur'an illiteracy. The study results from show that interpersonal communication effectively reduces Al-Qur'an illiteracy because the recognition of Al-Qur'an letters and how to read the Al-Qur'an are conveyed and corrected directly. In this case, the House of Qur'an Fatima Al-Fihri uses teaching and coaching communication methods using interpersonal communication methods that occur face to face. This method of communication in the process of learning and teaching the Qur'an is called Talaqqi or Musyafahah.